Fulfillment of Safety Needs and Efforts to Prevent Fall In Elderly - R. Siti Maryam; Rosidawati Rosidawati; Tien Hartini (Jurnal Riset Kesehatan, 2013)
This study aims to describe safety needs for the elderly in nursing home Region of DKI Jakarta. The method used survey with the nursing staff by 43 respondents and  the elderly by 53 respondents. The results found that the safety needs for the elderly in nursing home are good by 79.1 %; elderly aged around 60-95 years; 62.3 % female, have a history of falling 58.5 %, the biggest fall location of 45.2 % at  the street and 22.6 % in the bedroom, most of the elderly suffering from 98.1 % (like hypertension, arthritis, diabetes, asthma, gastritis, etc.); elderly have good attitude towards safety compliance by 56.6 %, the highest level of education officers are middle to lower by 67.4 %; the level of knowledge and a role for the fulfillment of the needs of the elderly are lacking a sense of safety is 53.5 % and 60.5 %; policies related nursing needs have good safety around 74.4 %.